Propuesta de mejora en una línea de producción de pañales desechables para niños - Valeriano Flores, Andrea Diana (2020)
The study proposes to demonstrate through engineering tools how to improve customer satisfaction with respect to the claims made in 2019 for irritation, which translates into potential consumer losses, directly impacting the positioning of the brand in the national market. The first part of the work carried out the diagnosis of the company to be evaluated, as well as the external and internal part. Determining the main problem, baby irritation, where consumer complaints increased considerably in 2019. The second part of the work will present possible solutions and improvements to be made in the process. These consist of carrying out a tactical improvement plan with prioritizations, redesign of the process, training for the teams, autonomous care cards and monitoring of the tasks of a multidisciplinary team. Finally, the solution will be developed, and the budget will be shown with the time necessary to complete the task. As a result of the work, there is a decrease in claims for irritation vs the year 2019, justifying the tasks performed.